Effect of Treating Expansive Soil with Lime - Salih, Sarah R.; Shafiqu, Qassun S. Mohammed (Al-Nahrain Journal for Engineering Sciences, 2024)
Expansive soil poses significant challenges for civil engineers worldwide since it seriously affects the structures built upon it. This soil has a very active group of minerals called montmorillonite, which is responsible for the significant volume change it exhibits. For a number of years, chemical additives have been utilized to stabilize soil, with various levels of success. Soil stabilization has involved the use of a variety of additives, including cement, lime, polymers, salts, and combinations of these. However, lime is very often used for expansive soil stabilization as it improves the soil’s mechanical properties. The effects of adding three percentages of lime (3%, 6%, and 9%) to expansive soil to improve its engineering properties are investigated through several tests. The laboratory tests consist of standard compaction, sieve analysis, atterberg limits, hydrometer, California bearing ratio, consolidation test, swelling potential, and specific gravity. The test results displayed that the plasticity index, liquid limit, swelling potential, and maximum dry density, specific gravity decreased using (3%, 6%, and 9%) lime. In contrast, the plastic limit, and optimum moisture content increased using (3%, 6%, and 9%) lime. The California bearing ratio is increased from (12.13% to 14.65%) by adding (9% L). The swelling index and compression index are decreased from (0.070 to 0.030) and from (0.581 to 0.193) respectively by adding (9% L). The swelling percentage is reduced from (18.77% to 6.03%) by adding (9% L).